Sistem Klasifikasi Tahu Putih Murni dan Tahu Putih Mengandung Formalin Menggunakan Metode K-Nearest Neighbor - Dede Satriawan; Hurriyatul Fitriyah; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Tofu is a food ingredient made from soybean deposits, and tofu is a type of food that does not last long after it is produced. Therefore, some tofu producers are not responsible for adding formaldehyde chemical to tofu so that tofu is more durable and not easily rot. Food containing formalin if consumed by the body is very dangerous to health in the short to long term. And if the body is exposed for a long period of time, it will cause damage to the kidneys, lymph, pancreas, liver, heart, and accelerate the aging process. To solve this problem it is necessary to design a system for the classification of pure white tofu and white tofu containing formalin using Arduino Mega hardware with input sensor from Grove-HCHO as a gas sensor, TCS3200 as a color sensor and the output will use LCD. And the accuracy of the system will be tested with the results with an average percentage error accuracy obtained from the sensor input is 1.20% for TCS3200 sensors, 4.26% for the Grove-HCHO sensor. For the classification of the K-NN method the percentage accuracy obtained is 83.33%.